Influence of Vacuum Heating on Wettability of Multiscale Structured Metal Coating Surface - Li, Jie; Pan, Wu; Li, Jihong; Zhang, Min (Journal of thermal spray technology, 2023)
In the present work, the coating surface subjected to heating in a vacuum drying oven without additional artificial modification exhibited a spontaneous change in its wettability from superhydrophilicity to superhydrophobicity. To clarify the mechanism of wettability transition and reveal the role of vacuum heating, plasma-sprayed metallic coatings with optimized biomimetic micro–nano-multiscale structure were taken as the research subjects. The influence of surface chemical composition on the wettability of coatings was emphatically studied via infrared spectroscopy and x-ray photoelectron spectroscopy. According to the results, the main reason for the wettability transition was the change in chemical state of the coating surface due to spontaneous adsorption of alkanes and alkyl chains with low surface free energy from the vacuum residual gas during vacuum heating. Heating promoted desorption of the initial physical adsorption layer and subsequent re-adsorption of residual gas, and vacuum system supplied the adsorbates, thereby providing the driving force for the spontaneous adsorption. The increase in heating temperature could promote re-adsorption of residual gas and improve the transition degree of wettability. The prepared superhydrophobic coatings had an excellent self-cleaning property. Therefore, this study not only opens up new prospects for rapidly achieving superhydrophobicity of surfaces, but also reveals the strong effect of vacuum drying on the surface wettability.